On the Isotopic Composition of Cold Pools in Radiative‐Convective Equilibrium. Issue 10 (17th May 2021) - Torri, Giuseppe
Abstract: Although stable water isotopologues are important tools in the study of the climate system, some of the physical processes that affect them are still imperfectly constrained. In this work, I concentrate on cold pools, essential components of deep convective systems that are arguably one of the least understood features from the water isotopologue perspective. Using a combination of a Lagrangian and an Eulerian framework, I first focus on quantifying how different processes determine the initial water vapor isotopic composition of cold pools. By analyzing the precipitation‐driven downdrafts that give rise to cold pools, I determine that mixing with environmental air has an enriching effect. On the other hand, microphysical processes tend to deplete the downdraft in the initial stages, mostly in the free troposphere, and to enrich it in the final stages, when the downdraft is in the subcloud layer. Then, I consider what processes might influence the isotopic composition of cold pools during their propagation, and I find that surface latent heat fluxes play a much greater role than cold pool entrainment. Finally, I show how water isotopologues could be used to diagnose the origin of water vapor in cold pool moist patches. Plain Language Summary: Water molecules exist in different species, called isotopologues, each containing different combinations of lighter and heavier varieties, or isotopes, of hydrogen and oxygen. Because these differences give molecules different chemical and physical properties, water isotopologues can reveal important information on the history of each air parcel and the physical processes that affected it. Here, I focus on cold pools, which are air currents near the surface that are generated by storms. Using computer simulations, I analyze how physical processes, such as the evaporation of rain or mixing between cold pools and air in the environment, affect the isotopes in cold pool water vapor. Key Points: Rain evaporation and equilibration effects deplete downdrafts in their initial stages and enrich them near the surface Latent heat fluxes play a greater role than mixing in enriching cold pools throughout their life cycle Stable water isotopologues could be used to diagnose the origin of water vapor in cold pool moist patches, but the signal may be small